RELASI ANTARA MATA PELAJARAN AKIDAH-AKHLAK PADA TRADISI BERANDEP - Dewi Nurhayati; Wahab Wahab (Universitas Islam Sultan Agung, 2019)
The culture of the Malay people of Sungai Jambu has local wisdom that is in the tradition of being deported in fields that are held once a year. Berandep in the fields is the activity of the Malay community in Sungai Jambu which is carried out in mutual cooperation at the time of planting (planting rice) and harvesting rice (tapping rice) with the aim of making the work is easier to finish. In the implementation of berandep formed 4-6 people and carried out in turns. In this study, researchers used a qualitative approach with ethnographic methods. Based on the tradition of research based on the above, that from the implementation of the tradition there are behaviors that lead to cooperation and helping one another, in the sense that the subject of continuous akidah-akhlak is based on tradition. The implementation of the backward tradition has a relation to the subjects of Akidah-Akhlak which are outlined in the material of cooperation, good help, and morals in neighboring and community life.Keywords: Local Wisdom, Akidah-Akhlak lessons, Berandep